1981
DOI: 10.1152/ajpgi.1981.240.1.g90
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal and metabolic effect of 1,25-dihydroxyvitamin D3 in normal adult rat

Abstract: We examined the effect of 1,25-dihydroxyvitamin D3 [1,25(OH)2D3] on intestinal 45Ca and [32P]phosphate uptake in normal and mineral- and vitamin D-replete adult rats. The results indicate that 45Ca uptake by adult rat duodenum was stimulated by "physiological" doses of 1,25(OH)2D3. With increasing dosage of 1,25(OH)2D3, 45Ca uptake also became stimulated first in the colon and then in the jejunum and ileum. The increase in duodenal and jejunal 45Ca uptake was paralleled by an increase in [32P]phosphate uptake,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 0 publications
3
17
0
Order By: Relevance
“…In the present study, no significant difference was observed between the level of 25(OH)D3, the precursor of 1,25(OH)2D3, in any of the four groups of animals and the absolute levels ('.30 ng/ml) were similar to those reported by Schedl et al (9) (24,25). The observation that the response ofthe 20-24-wk-old SHR Jm.s to low dietary calcium was significantly impaired compared to that of the WKY (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, no significant difference was observed between the level of 25(OH)D3, the precursor of 1,25(OH)2D3, in any of the four groups of animals and the absolute levels ('.30 ng/ml) were similar to those reported by Schedl et al (9) (24,25). The observation that the response ofthe 20-24-wk-old SHR Jm.s to low dietary calcium was significantly impaired compared to that of the WKY (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…A substantial amount of endogenous calcium was also found in the distal small intestine which is the main site for calcium secretion (18,19). Since the colon is a site of calcium absorption rather than calcium secretion (20,21), the endogenous calcium present in the colon probably resulted from a transit from the distal small intestine. Consistent with our previous in situ investigation (3), the present in vivo study demonstrated that ethanol markedly stimulates gastric calcium secretion and suppresses calcium absorption in the proximal small intestine (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although little is known about 1,25(OH) 2 D 3 action in other parts of the intestine, the importance of regions other than the proximal small intestine has been suggested. Vitamin D and 1,25(OH) 2 D 3 -regulated calcium transport has been reported in ileum, cecum, and colon as well as duodenum (140,141,250). The highest expression levels of TRPV6 are in the distal intestine (517).…”
Section: Vitamin D and The Distal Intestinementioning
confidence: 98%